Science-Based Approaches to Respond to COVID and Other Public Health Threats - Guerrero, Erick (IntechOpen, 2021)
COVID-19 and other public health threats have contributed to more than six million deaths globally in a short amount of time. As such, there is an urgent need to respond to these threats in a way that improves global health and wellbeing. Written by a diverse group of exemplary scientists, the thirteen chapters in this volume provide unique, comprehensive, and science-based approaches to respond to macro-structural, human process, and micro issues affecting public health threats.